AB1127 Pulmonary arterial hypertension and posterior reversible encephalopathy syndrome (PRES) in a patient with adult onset still's disease. (12th June 2018) - Khan, A.; Bhamra, K.; El-Ghazali, S.; Adler, M.
Abstract : Background: Pulmonary arterial hypertension is a rare complication of AOSD and there are only a limited number of case reports in the literature. PRES is a rare acute neurological condition characterised by rapid onset of headache, seizures, altered consciousness, visual disturbances and usually very high blood pressure. Brain imaging characteristically shows high signal change in the subcortical white matter, predominantly in the posterior lobes which normalises within days to weeks. There are rare case reports of seizures and other neurological manifestations associated with AOSD but no published case reports of classic PRES. Objectives: To share this interesting case with our rheumatology colleagues. Methods: We present a case of 24 year old Afro-Caribbean lady, diagnosed with AOSD in December 2015, presenting with recurrent fevers, weight loss, polyarticular synovitis, small volume lymphadenopathy, evanescent urticarial rash, hyper-ferritinemia (3700 ug/L) and raised CRP (146 mg/L). Rheumatoid factor, ANA, CCP, ENA and ANCA were negative. Infection screen was negative including blood-borne viruses and whole-body imaging was normal. She was initially treated with pulsed Methylprednisolone 1 g IV for 3 days followed by 40 mg oral prednisolone. She had a good initial response (ferritin 1700 ug/L, CRP 36 mg/L), but subsequently we were unable to reduce her prednisolone below 35 mg due to recurrence of symptoms. She had quite a stormy course over the rest of the year with a number of hospital admissions and her ferritin running as high as 35, 000 ug/L and CRP more than 200 mg/L. In February 2017 she had a further severe flare and was started on Anakinra. She initially responded well (Ferritin 400 ug/L, CRP 3 mg/L), but four months later started to flare again, requiring a further admission, treated with IV Methylprednisolone. She was switched from Anakinra to Tocilizumab but was stopped after 4 doses due to poor response. Following development of exertional dyspnoea, echocardiography and right heart catheter studies demonstrated a raised mean pulmonary artery pressure of 42 mmhg with severe TR, right sided volume overload and a BNP of 8741 ng/L warranting referral to the regional PAH centre. She also developed peripheral sensorimotor neuropathy in her lower limbs confirmed by NCS. Results: In December 2017 she was admitted with severe shortness of breath, hypoxia and a ferritin of over 15, 000 ug/L. She developed seizures with status epilepticus, very high blood pressure and ended up requiring mechanical ventilation. MRI and CT brain were suggestive of PRES with subcortical high signal change and symmetrical vasogenic oedema in occipital and parietal lobes. She was treated in Neuro ITU with anti-epileptics, anti-hypertensives, IV hydrocortisone and Anakinra was restarted. She made a rapid and full neurological recovery with resolution of changes on her brain scans. She continues Anakinra, and Cyclosporine 2 mg/kg body weight has been added since. She has also been started on Tadalafil 20 mg BD for her pulmonary arterial hypertension. Prednisolone has been tapered to 15 mg and she is clinically well with a CRP of 26 mg/L and ferritin of 2600 ug/L. Conclusions: We present a case of life threatening AOSD complicated by pulmonary arterial hypertension, PRES and peripheral neuropathy. She has unusually severe disease, which is quite refractory to treatment and has been associated with rare manifestations. Disclosure of Interest: A. Khan Shareholder of: No, Grant/research support from: No, Consultant for: No, Employee of: No, Paid instructor for: No, Speakers bureau: No, K. Bhamra: None declared, S. El-Ghazali: None declared, M. Adler: None declared